The data processing and analysis methods for stratospheric ozone and planetary wave study - Shi, Y.; Evtushevsky, O.; Milinevsky, G.; Grytsai, A.; Klekociuk, A.; Ivaniha, O.; Andrienko, Yu. (Ukrainian Antarctic Journal, 2022)
We describe the methods and data sources for investigating the stratospheric ozone and planetary waves in the atmosphere in the framework of research provided by our international team. Selected ground-based and satellite instruments for ozone measurements and related reanalyses are described. Examples of data and analysis tools are shown. The technique of planetary wave spectral analysis under conditions of dynamic changes during sudden stratospheric warmings is presented. A brief description of the main results, obtained with the participation of the authors, using combined methods of analysis are considered. We describe procedures for the investigation of a long-term eastward displacement of the zonal ozone minimum over the Antarctic in the spring months, analysis of the spatial and temporal characteristics of the teleconnection between the tropical thermal source and the Antarctic stratosphere, and the creation of the predictive index used for the forecast of possible ozone hole anomalous development in spring months. Examples of application of analysis methods to retrieve the changes in the zonal asymmetry of the Arctic stratopause and features of the annual ozone cycle in connection with zonal ozone asymmetry are discussed.